2012
DOI: 10.1155/2012/689807
|View full text |Cite
|
Sign up to set email alerts
|

Supported Nanosizedα-FeOOH Improves Efficiency of Photoelectro-Fenton Process with Reaction-Controlled pH Adjustment for Sustainable Water Treatment

Abstract: The overall photoelectro-Fenton (PE-Fenton) process for water treatment with neutral initial pH includes three steps of pH reduction, PE-Fenton reaction, and pH elevation. Reaction-controlled pH adjustment (RCpA), which utilizes the intrinsic electrochemical reactions instead of chemical addition, has been employed to lower the pH, maintain the lowered pH for the Fenton reaction, and recover the pH for final effluent discharge. This study demonstrated that the overall efficiency of this sustainable PE-Fenton p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…The broad reflection at 2θ = 20-25 • is indicative of amorphous biochar and is consistent with other unmodified biochars of poor crystallinity reported in the literature [61,62]. In the pattern corresponding to Fe-BC-500, the intense peak at 2θ = 23.3 • corresponds to the (110) plane of α-FeOOH, whereas the peak at 2θ = 25.5 • is attributed to the (012) plane of α-Fe 2 O 3 [63]. The major peak at 2θ = 35.45 • corresponds to the crystalline plane with a Miller index of (311).…”
Section: Biochar Characterizationsupporting
confidence: 88%
See 1 more Smart Citation
“…The broad reflection at 2θ = 20-25 • is indicative of amorphous biochar and is consistent with other unmodified biochars of poor crystallinity reported in the literature [61,62]. In the pattern corresponding to Fe-BC-500, the intense peak at 2θ = 23.3 • corresponds to the (110) plane of α-FeOOH, whereas the peak at 2θ = 25.5 • is attributed to the (012) plane of α-Fe 2 O 3 [63]. The major peak at 2θ = 35.45 • corresponds to the crystalline plane with a Miller index of (311).…”
Section: Biochar Characterizationsupporting
confidence: 88%
“…α-Fe2O3 [63]. The major peak at 2θ = 35.45° corresponds to the crystalline plane with a Miller index of (311).…”
Section: Biochar Characterizationmentioning
confidence: 99%
“…60,61 Furthermore, a comparison of the Raman spectra of fresh and postcatalytic FCP350 in Figure 6a shows the presence of a weak M−OOH peak at around 509 cm −1 and a broad M−OOH band at 950−1050 cm −1 in the postcycled catalyst. 62,63 Thus, the evolution of oxygen through eq 3 is concomitant with the validation of eq 2. 3 An extensive and active formation of in situ metal oxy-hydroxides as characteristics of our presented FeCoP nanorods leads to an excellent OER activity with an exceptionally high current density at a low overpotential, a low Tafel slope, and extended stability.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to these, the in situ metal oxy-hydroxide formation is confirmed by conducting the slow-scan XRD measurement in the 13–43° 2θ range on the postcycled FCP350. The XRD patterns of the fresh and slow-scan postcatalytic catalysts are compared (Figure S11), and it is found that the slow-scan XRD pattern shows weak-intensity diffraction peaks of M­(Fe/Co)–OOH at 17–25 and 26.35°. , Furthermore, a comparison of the Raman spectra of fresh and postcatalytic FCP350 in Figure a shows the presence of a weak M–OOH peak at around 509 cm –1 and a broad M–OOH band at 950–1050 cm –1 in the postcycled catalyst. , Thus, the evolution of oxygen through eq is concomitant with the validation of eq . An extensive and active formation of in situ metal oxy-hydroxides as characteristics of our presented FeCoP nanorods leads to an excellent OER activity with an exceptionally high current density at a low overpotential, a low Tafel slope, and extended stability.…”
Section: Resultsmentioning
confidence: 99%
“…Diatomite has also been employed as a catalyst support for several reactions: oil hydrogenation [14], hydration of acrylonitrile [15], Fischer-Tropsch synthesis [16], hydrocarbons oxidation [1], photodegradation of industrial wastes [17,18], photoelectroFenton of industrial wastewaters [19], and phenol hydroxylation [20]. Nevertheless, the use of diatomite as a catalyst rather as catalyst support has not been extensively studied [21], although, the presence of a high percentage of iron would enable its use as a heterogeneous Fenton-like catalyst without requiring major modifications.…”
Section: Introductionmentioning
confidence: 99%